2018
DOI: 10.1002/slct.201801446
|View full text |Cite
|
Sign up to set email alerts
|

N‐ and P‐co‐doped Graphite Felt Electrode for Improving Positive Electrode Chemistry of the Vanadium Redox Flow Battery

Abstract: In this study, N-and P-co-doped carbon derived from microcrystalline cellulose, and diammonium hydrogen phosphate ((NH 4 ) 2 HPO 4 ) were employed as the catalyst for VO 2þ /VO þ 2 redox reaction. Doping with P enhanced the onset potential and the presence of N (in the form of pyridinic-and pyrrolic-N) and P together enhanced the peak current for the VO 2þ /VO þ 2 redox reaction. Further, the doping improved the wettability of the catalyst, thereby increasing the interfacial area available for the reaction. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Water uptake for HA-35 was found to be 41.5%, and 46% for the HA-45 membrane. 41,42 The enhancement in water uptake was due to the presence of large number of functional groups in the HA-45 membrane compared to the HA-35 membrane, and the functional groups also increased water uptake ( Table 1). The expansion was proportional to the water uptake, and as the water uptake increased, the membrane expansion also increased, and the valencies of hydrophobic and hydrophilic regions maintained the expansion ratio and only 22% for HA-35 and 28% for HA-45 was noted, which was quite reasonable for IEMs.…”
Section: Water Uptake Behaviour and Transport Properties Of The Membrmentioning
confidence: 99%
See 1 more Smart Citation
“…Water uptake for HA-35 was found to be 41.5%, and 46% for the HA-45 membrane. 41,42 The enhancement in water uptake was due to the presence of large number of functional groups in the HA-45 membrane compared to the HA-35 membrane, and the functional groups also increased water uptake ( Table 1). The expansion was proportional to the water uptake, and as the water uptake increased, the membrane expansion also increased, and the valencies of hydrophobic and hydrophilic regions maintained the expansion ratio and only 22% for HA-35 and 28% for HA-45 was noted, which was quite reasonable for IEMs.…”
Section: Water Uptake Behaviour and Transport Properties Of The Membrmentioning
confidence: 99%
“…[37][38][39] Due to the highly oxidative and reducing environment of the catholyte and anolyte in the VRFB it is very difficult to sustain the stability of the membrane as there may be a possibility of leaching of the fillers. [40][41][42][43] Maintaining stability of the membrane without compromising the ionic conductivity in the VRFB environment is an important parameter.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, heteroatom doping was effective on the increase of active sites and regulation of electron distribution [ 18 , 19 , 20 , 21 , 22 ]. It has been demonstrated that co-doping multi elements with different electronegativity can remarkably improve the performance of graphene due to the positive synergistic effect of heteroatoms [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Ci et al [ 35 ] simultaneously doped graphene with nitrogen and loaded cobalt to obtain Co/NG catalyst by heat treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A majority of the research on developing electrodes via heteroatom doping focuses on introducing single heteroatoms to carbon materials. To the best of our knowledge, in the field of VRFBs, only few studies have investigated N, P co‐doped carbon materials as electrocatalysts for V 4+ /V 5+ redox reaction 33,36 . They reported that the V 4+ /V 5+ redox reaction can be effectively enhanced by introducing N, P co‐doped carbon materials as electrocatalysts on the carbon felt electrode.…”
Section: Introductionmentioning
confidence: 99%
“…12 Carbonaceous materials co-doped with binary heteroatoms show enhanced electrochemical activity for the oxygen reduction reaction at the cathodes of fuel cells and metal-air batteries because of the increased total number of heteroatoms and the synergetic effect of the co-doped heteroatoms. 25,29,[32][33][34] Interestingly, despite extensive studies on N, P co-doped carbon materials, these carbon materials have rarely been explored for improving the electrochemical performances of VRFBs. A majority of the research on developing electrodes via heteroatom doping focuses on introducing single heteroatoms to carbon materials.…”
Section: Introductionmentioning
confidence: 99%